Insecurity and political values in the Arab world. Issue 5 (3rd July 2020) - Cammett, Melani; Diwan, Ishac; Vartanova, Irina
ABSTRACT: Within a few years of the historic Arab uprisings of 2011, popular mobilization dissipated amidst instability in many Arab countries. We trace the relationship between shifting macro-political conditions and individual-level political values in the Middle East, demonstrating that a preference for democracy and political trust are not fixed cultural features of populations but rather can shift rapidly in the face of perceived insecurity. Our empirical analyses employ longitudinal data from the Arab Barometer covering 13 countries and data from the 2015 World Values Survey, which includes both Arab and non-Arab countries in order to benchmark regional developments against global patterns. Our findings contribute to the growing body of research on the political effects of insecurity and oppose culturalist depictions of fixed political attitudes among Muslims in narrow perspectives on the relationship between Islam and democracy.